(untitled) (Applied Biological Research, 2025)
The Subarnarekha river, known as the "Golden River" of the Chotanagpur Plateau in Jharkhand (India), is adversely impacted by industrial effluents and anthropogenic activities, threatening its aquatic biodiversity. This study assessed the seasonal variations in physicochemical properties and their influence on the growth, survival, and biomass of Indian white prawn (Fenneropenaeus indicus) at two sites in East Singhbhum, i.e., Site I (Mango, Jamshedpur) and Site II (Galudih, Ghatshila), from July 2019 to June 2022.The water quality-related physicochemical parameters (temperature, pH, dissolved oxygen, and salinity) were monitored seasonally, and their correlations with prawn survival rate, mean body weight, length, and biomass production were analyzed using Pearson’s correlation coefficient and regression analysis. The results revealed notable seasonal fluctuations in physicochemical parameters, particularly water temperature and salinity, which exhibited strong positive correlations with prawn growth metrics.Site II consistently exhibited higher mean body weight, survival rate, and biomass production compared to Site I, with optimal growth observed during the spring season. Water temperature showed a strong positive correlation with growth metrics, while salinity played a crucial role, particularly influencing survival and biomass.The findings highlight that physicochemical parameters—especially temperature and salinity—significantly impact the growth and productivity of F. indicus in the Subarnarekha river. These findings underscore the importance of regular water quality monitoring for sustaining aquaculture practices in riverine ecosystems impacted by pollution. Effective management of pollution sources is essential to conserve the river’s health and support the livelihoods dependent on its aquatic resources.